A double-edged sword of using opioids and COVID-19: a toxicological view - Mahshid Ataei; Farshad M. Shirazi; Roland J. Lamarine; Samaneh Nakhaee; Omid Mehrpour (Substance Abuse Treatment, Prevention, and Policy, 2020)
Abstract Today, COVID-19 is spreading around the world. Information about its mechanism, prognostic factors, and management is minimal. COVID-19, as a human disease, has several identifying phases. Physicians of patients with COVID-19 may be interested in knowing whether opioid use disorder may affect their patients’ course or prognosis. This information may be crucial when considering the opioid epidemic in the US and other parts of the world. Opioid use at high doses and over several months duration can mitigate the immune system’s function, which may complicate the course of COVID-19 disease. Potential suppression of parts of the immune response may be important in prevention, clinical support, and therapeutic use of medications in various phases of the COVID-19. Specifically, opioid use disorders via an inhalation route may enhance the “late hyper-inflammatory phase” or result in end-organ damage. It is well established that opioids decrease ventilation as their effect on the medullary respiratory centers increases the risk of pneumonia. This increased risk has been associated with immune-suppressive opioids. The ultimate role of opioids in COVID-19 is not clear. This paper endorses the need for clinical studies to decipher the role and impact of chronic opioid use on viral diseases such as COVID-19.